Effect of Growth Regulations on Flower and Fruit Drop in Chilli - Sreeja Rajendran (Department of Plant Physiology, College of Agriculture, 2000)
Investigations were carried out at the Department of Plant Physiology, College of Agriculture, Vellayani during December 1999 to March 2000 to find the effect of growth regulators viz. IAA, NAA, Triacontanol and GA in controlling flower and fruit drop in chilli var. ', Jwalasakhi. IAA, NAA and GA were used at concentrations of 10, 20, 30 and 40 ppm while Triacontanol was used at 1,2, 3 and 4 ppm. Two controls were also provided, one with distilled water spray and the other with no spray. Two sprays of growth regulators were given, one at 20 days after transplanting and the other at 40 days after transplanting. The effect of these growth regulators on morphological, growth, physiological, biochemical and yield parameters were also studied. The growth regulators produced considerable variation with respect to intensity of flowering, flower drop, fruit set and fruit drop. The flower production was increased upto 45.5 per cent with IAA 30 ppm. IAA 40 ppm was most effective in reducing the flower drop by 48.06 per cent increasing the fruit set by 69.18 per cent when compared to control (water spray). NAA 30 ppm induced earliness in flowering (23.17 days) and GA at 40 ppm showed the maximum plant height (38.93 cm). The plants treated with GA 40 ppm showed the maximum leaf area (478.04 cm2 plant"! ) and leaf area index (0.23). NAA 20 ppm recorded the highest specific leaf weight (l.30 g m-2)and IAA 30 ppm, the maximum leaf area ratio (l.08 m-2 g-l). The plants sprayed with Triacontanol 2 ppm showed